2013
DOI: 10.1103/physreva.87.043602
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-limited measurement of magnetic-field gradient with entangled atoms

Abstract: We propose a method to detect the microwave magnetic-field gradient by using a pair of entangled two-component Bose-Einstein condensates. We consider the two spatially separated condensates to be coupled to the two different magnetic fields. The magnetic-field gradient can be determined by measuring the variances of population differences and relative phases between the two-component condensates in two wells. The precision of measurement can reach the Heisenberg limit. We study the effects of one-body and two-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…Such a kind of dissipations is well described by one-body atom losses 21 27 . Thus the dissipative phase accumulation obeys a Markovian master equation 34 35 36 38 39 40 41 42 43 ,…”
Section: Resultsmentioning
confidence: 99%
“…Such a kind of dissipations is well described by one-body atom losses 21 27 . Thus the dissipative phase accumulation obeys a Markovian master equation 34 35 36 38 39 40 41 42 43 ,…”
Section: Resultsmentioning
confidence: 99%
“…Both of these two sets of quantum states are orthonormal eigenstates of the coherence operator expressed as , see Ref. 25 . To implement these two von Neumann measurements in experiment, it requires performing global operators on N atoms instead of local operators on each atom.…”
Section: Resultsmentioning
confidence: 99%
“…A standard measuring instrument for determining the gradient is differential atom interferometry, which utilizes two completely polarized atomic ensembles. Recently, quantum-enhanced measurements of magnetic field gradient have been proposed 22 23 24 25 .…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] For a multiparticle system of cold atoms, it has been demonstrated that quantum entanglement and spin squeezing can be prepared by employing intrinsic inter-atom interactions or laser induced artificial inter-atom interactions. [27][28][29] Up to now, cold atoms have been widely used for implementing precision metrology, such as interferometers, [30][31][32] gyroscopes, 33 quantum clocks, [34][35][36] magnetic field detectors [37][38][39][40] and micro-gravity sensors. [41][42][43][44] In this chapter, we review the recent progresses in quantum metrology with cold atoms.…”
Section: Introductionmentioning
confidence: 99%